Side Effects of bb-Interferon: A Comparative Study Among Avonex, Betaseron and Rebif: Side effects of b-interferon - Etemadifar, Masoud; Basiri, Keyvan; Tavakoli, Naser (Iranian Journal of Pharmaceutical Sciences, 2005)
The administration of b-interferon is a recognized treatment for multiple sclerosis. The frequency of side effects is an important factor in drug or product selection. In this study, the side effects of three available b-interferon products are compared in 122 multiple sclerosis patients who were treated with b-interferon products for at least three months and had the Expanded Disability Status Scale (EDSS) between 1 and 6. The frequencies of side effects were determined for each group and the collected information were compared in the three treated groups. Fever, chills, headache, malaise and asthenia were the most frequent observed complications. Necrosis at the injection site was seen only in Betaseron group. Somnolence was more frequent with the administration of Avonex. Gastro-intestinal disturbances were less frequent in patients treated with Rebif. Weight gain was more frequent in patients treated with Avonex, and seizure and migraine were observed only in this group.Urticaria and hypersensitivity skin reactions were less frequent with the administration of Avonex. Rebif may be a better choice for patients with gastrointestinal disturbances, suicidal attempts and chronic fatigue syndrome. Avonex may be better tolerated in patients with a history of urticaria and hypersensitivity skin reactions, but it is less recommended for patients with a history of seizure, migraine and syncope. Betaseron may be a better choice in patients with a history of chest pain and hypertension.